2014
DOI: 10.3892/ol.2014.1931
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor microRNA-34a inhibits cell proliferation by targeting Notch1 in renal cell carcinoma

Abstract: MicroRNA-34a (miR-34a) is a tumor suppressive microRNA, which induces G1 arrest, apoptosis and senescence by repressing the expression of multiple oncogenes. This study aimed to investigate the biological function and molecular mechanisms of miR-34a in human renal cell carcinoma (RCC) cells. Quantitative polymerase chain reaction (qPCR) revealed that miR-34a expression was significantly downregulated in eight of the 10 (80%) RCC tissues compared with adjacent normal tissues. In RCC cell lines, several other ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…with the normal tissues, which suggested that dysregulation of miR-34a may be involved in the development of human esophageal cancer. Moreover, studies have reported that miR-34a can affect the growth of proneural glioma and renal cell carcinoma cells (13,24). In the present study, we found that TE-1 cells grew slowly following transfection with .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…with the normal tissues, which suggested that dysregulation of miR-34a may be involved in the development of human esophageal cancer. Moreover, studies have reported that miR-34a can affect the growth of proneural glioma and renal cell carcinoma cells (13,24). In the present study, we found that TE-1 cells grew slowly following transfection with .…”
Section: Discussionsupporting
confidence: 63%
“…It has been reported that miR-34a expression was significantly reduced in non-small cell lung cancer compared with normal tissues (12). miR-34a induces G1 arrest, apoptosis and senescence by repressing the expression of Notch1 in RCC cell lines, and inhibit gastric cancer tumorigenesis by targeting PDGFR and MET through the PI3K/Akt pathway (13,14). miR-34a, which is located at chromosome 1p36, is a well-known tumor-suppressor miRNA present in various types of human cancer (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…In 5 and 20 mM metformin-treated cells, the levels of miRNA34a expression were 1.66- and 2.46-fold greater, respectively, compared with the levels in the control group (Figure 4B). In some previous studies, miRNA34a has been shown to be capable of inhibiting cell proliferation in renal cancer cells [15,16]. These data implied that the upregulation of miRNA34a induced by metformin probably contributed to the inhibitory effect of metformin on cell proliferation in ACHN cells.…”
Section: Resultsmentioning
confidence: 64%
“…28,29 Beyond that, a report's analysis articulated that miR-34a inhibited cell proliferation by targeting Notch1 in renal cell carcinoma. 30 Meanwhile, other reports suggested that P53 could combine with the promoter of miR-34a and activate its transcription. P53 mutate could inhibit miR-34a transcription activation and result in a lower expression of miR-34a.…”
Section: Discussionmentioning
confidence: 99%